2015
DOI: 10.1586/14737175.2015.1058162
|View full text |Cite
|
Sign up to set email alerts
|

Oral drugs in multiple sclerosis therapy: an overview and a critical appraisal

Abstract: Multiple sclerosis (MS) is characterized by demyelination and axonal loss that results in progressive disability. Recent advances in understanding the immune pathogenesis of MS resulted in the introduction of numerous effective drugs with diverse mechanisms of actions, routes of administration and benefit-risk profiles. New oral drugs recently approved for MS treatment has led to significant achievements in MS management. The oral route of administration promotes patient satisfaction and increases therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 144 publications
(215 reference statements)
0
21
0
1
Order By: Relevance
“…In this regard, no attention has been paid on men's fertility status in either research or clinical practice. In the pursuit of a personalized treatment, future studies are needed to clarify the impact of new DMTs on spermatogenesis and male fertility (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, no attention has been paid on men's fertility status in either research or clinical practice. In the pursuit of a personalized treatment, future studies are needed to clarify the impact of new DMTs on spermatogenesis and male fertility (23,24).…”
Section: Discussionmentioning
confidence: 99%
“… 1 In the past 5 years, therapeutic options for treating relapsing remitting MS (RRMS) have impressively broadened and new oral first-line agents have been approved. 2 , 3 In European countries, delayed-release dimethyl fumarate (DMF), also known as gastro-resistant DMF, and teriflunomide (TRF) are used in the treatment of persons with RRMS (pwRRMS). 3 Pivotal trials have demonstrated the benefits of DMF and TRF on both clinical symptoms (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro the investigators reported that siponimod reduced the release of IL-6 from activated microglial cells in addition to astrogliosis and microgliosis reduction. The potential neuroprotective effect of siponimod suggested by these studies could explain the benefit observed on disability progression in patients with secondary progressive MS treated with this drug [10,18].…”
Section: Bodymentioning
confidence: 82%
“…These are cell populations that have been shown to co-express latent EBV proteins and support a role for EBV infection in B-cell activation in MS brain [9]. This will need to be elucidated further [10].…”
Section: Bodymentioning
confidence: 97%